It Takes a Village!: Customer Value Co-Creation Behavior in Restaurant Social Media-Based Brand Community - Song, Jahyun; Qu, Hailin; (Robert) Li, Xiang (Journal of hospitality & tourism research (Washington, D.C.), 2024)
Customers’ value co-creation behavior plays an essential role on brand pages, which many hospitality firms adopt to create value with customers. However, current understanding of the elements, drivers, and dynamics of such behavior is limited. Based on the value co-creation literature, motivation–opportunity–ability theory, and the dual identification framework, this study sought to bridge this knowledge gap. Specifically, this research clarified customer engagement behavior (CEB) and customer citizenship behavior (CCB) as respective in-role and extra-role behaviors of value co-creation and revealed their positive relationship. Structural equation modeling indicated that motivations (seeking assistance and diversion), social presence, and brand knowledge positively influenced CEB, which then affected CCB directly and indirectly through customer–brand identification. Moreover, functional benefits did not trigger meaningful CEB, and customer–community identification had a minimal impact on CCB. Overall, these insights can help practitioners manage their brand pages more effectively to co-create value with customers.